Is Balance Control Affected by Sleep Deprivation? A Systematic Review of the Impact of Sleep on the Control of Balance - Umemura, Guilherme Silva; Furtado, Fabianne; Santos, Fabia Camile dos; Gonçalves, Bruno da Silva Brandão; Forner-Cordero, Arturo (Frontiers in Neuroscience, 2022)
Background: Sleep is a complex physiological function that should be addressed from different perspectives and consider the circadian rhythm. Sleep deprivation, either acute or chronic, negatively affects several functions, including motor control. Balance control is essential in several daily life activities and balance problems are related to falls. Research question: This review focuses on how sleep conditions impact balance control. Methods: Systematic literature review according to PRISMA guidelines. Results: The reviewed literature provided evidence that acute sleep deprivation is associated with balance and postural instability. Furthermore, balance control measurements can be used to detect sleepiness and fatigue. We also found that there is scarce literature about the effects of circadian rhythms chronic sleep restriction, a frequent problem, on balance control. Sleep deprivation is a multifaceted problem that depends on the number of sleeping hours and the quality of sleep. Most of the studies only consider one-night (acute) sleep deprivation without monitoring prior sleep conditions and the circadian rhythm phase of the participants. However, the few studies that monitored chronic sleep restriction and circadian rhythm phase showed that these factors affect balance control. Significance: These results suggest that the sleep conditions of a subject should be considered for several days prior to balance control tests. Therefore, we propose a revision of current postural measurement protocols to include sleep assessment, such as sleep quality questionnaires or actimetry, and to consider the circadian rhythm of the participants to plan the hour of the tests.